Synthesis and evaluation of both phosphonic- and bisphosphonic acid functionalized monomers for longer - lasting dental fillings - Gençoğlu, Türkan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
It is possible to increase the lifetime of dental restorations by improving the performaces of ‘self-etching’ adhesives and/or dental composites. In this work, the first monomers containing both phosphonate and bisphosphonate or phosphonic and bisphosphonic acid functionalities were synthesized for stronger interaction with tooth structure; and their properties were analyzed. For the synthesis of monomers, two amines (A1 and A2) having both phosphonate and bisphosphonate functionalities were synthesized. Reaction of these amines with with acryloyl chloride gave two novel acrylamide monomers (AAm-1 and AAm-2) with both phosphonate and bisphosphonate. It was impossible to synthesize acid derivatives of these monomers due to disappearance of double bonds; but their copolymers with poly(ethylene glycol)methyl ether methacrylate containing both phosphonic and bisphosphonic acid were obtained. Reaction of the same amines with 2-isocyanatoethyl methacrylate gave two novel methacrylate monomers (MA-A1 and MA-A2) with both phosphonate and bisphosphonate. By deprotection of phosphonate and bisphosphonate ester groups of MA-A1 and MA-A2, two novel methacrylates (MA-A1-Ac and MA-A2-Ac) with both phosphonic and bisphosphonic acid were synthesized. Copolymerization reactivities of the synthesized monomers with 2-hydroxyethyl methacrylate (HEMA) and bisphenol A glycidyl methacrylate (Bis-GMA)/triethyleneglycol dimethacrylate (TEGDMA) mixtures were investigated with real-time FTIR or photo differential scanning calorimetry. The acid monomers were found to have mild self-etching (pH = 1.65 ve 1.66) primer properties. Scanning electron microscopy (SEM) revealed that they can partially remove the smear layer on dentin and cause demineralization. X-Ray Diffractometer (XRD), FTIR and X-ray photoelectron spectroscopy (XPS) analyses of MA-A2-Ac-treated HAP particles (representative of tooth) showed formation of stable monomer-Ca salts. The acid monomers were found to be suitable for use in dental adhesives due to their solubilities in water, etching abilities, high copolymerization reactivities and their strong interaction with HAP. Addition of these monomers to dental composites is expected to improve longetivity of dental restorations.
Keywords: Fillings (Dentistry); Phosphonic acids.